Associative Classification with Classification Based Association (CBA) Algorithm on Transaction Data with Rshiny - Frederika, Alesia Arum; Bayupati, I Putu Agung; Buana, Wira (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2023)
Data mining can be used for businesses with large amounts of data. One of the data mining techniques is A ssociative Classification. It is a new strategy in data processing that combines association and classification techniques to build a classification model. This research used an associative classification technique on sales transaction data of Frozen Food Stores, which had sales transaction data on their business activities. It would be used in sales strategies to find items often purchased by class customers, namely, members and general. This research aimed to classify based on association rules using the CBA (Classification based Association) algorithm on sales transaction data. The application used the R programming language that business owners could use. The results of the rules obtained from the trial had the value of support, confidence, coverage, and lift ratio, which were the best value levels of a rule. The results of the rules that had the highest lift ratio value from all the data that have been inputted can be used as a reference to be implemented in sales strategies in knowing consumer needs.